STUDI KORELASI TINGKAT PENERAPAN TEKNOLOGI PASCA PANEN DENGAN TINGKAT PRODUKSI PADI SAWAH DI KABUPATEN LOMBOK BARAT - I DEWA GEDE SUARTHA; THOMAS BULU KALEKA; I GUSTI AGUNG DIDIT EKA PERMADI (SOSIAL SAINS DAN TEKNOLOGI, 2022)
Research on the Correlation Study of Post-Harvest Technology Application Levels with Production Levels focuses on the problem, whether there is a relationship between the two variables. To answer this question, a study was conducted in West Lombok Regency with a total of 42 farmers who were determined by side stratified random based on the status of their farmer group. The analytical tool used to determine the correlation between the level of application of post-harvest technology and the level of lowland rice production is the non-parametric statistic Cotingency Coefficient (Cc).The results of the analysis show that the level of application of post-harvest technology with the level of lowland rice production in West Lombok Regency has a positive correlation, with a Contingency Coefficient (Cc) of 0.89.